2019
DOI: 10.1038/s41598-019-46815-3
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient evidence for BMAA transfer in the pelagic and benthic food webs in the Baltic Sea

Abstract: The evidence regarding BMAA occurrence in the Baltic Sea is contradictory, with benthic sources appearing to be more important than pelagic ones. The latter is counterintuitive considering that the identified sources of this compound in the food webs are pelagic primary producers, such as diatoms, dinoflagellates, and cyanobacteria. To elucidate BMAA distribution, we analyzed BMAA in the pelagic and benthic food webs in the Northern Baltic Proper. As potential sources, phytoplankton communities were used. Pela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In other studies of fish collected in the Baltic Sea, the Eastern North Atlantic, and the Mediterranean Sea, no BMAA was detected in the fish muscle [16,26,28,61].…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…In other studies of fish collected in the Baltic Sea, the Eastern North Atlantic, and the Mediterranean Sea, no BMAA was detected in the fish muscle [16,26,28,61].…”
Section: Resultsmentioning
confidence: 71%
“…BMAA contents in organisms may vary, depending on the methodological differences between studies, inter-specific variations in their trophic status, geographical and seasonal parameters, and ecological responses of its producers [37]. Thus, as previously documented for fish [16,25,26,28,32,60,61], dolphins of certain geographical areas might also contain higher concentrations of BMAA than others. Accordingly, Davis et al (2019) reported three-fold higher concentrations of total BMAA in dolphins stranded in Florida than in dolphins from Massachusetts [45].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, BSIA helped to elucidate the role of microbial food webs and zooplankton grazing strategies (e.g., Rolff 2000 ; Eglite et al 2018 ; Motwani et al 2018 ) as well as benthic feeders (e.g., Limén and Ólafsson 2002 ; Karlson et al 2014 ) in the transfer of diazotrophic nitrogen, whereas CSIA was used to elucidate the role of complex biochemical processes and cyanobacterial supply of de novo synthesized amino acids for planktonic food webs (e.g., Loick-Wilde et al 2012 , 2018b ; Eglite et al 2019 ). Moreover, SIA studies addressed cyanobacterial toxins in fish (e.g., Lesutienė et al 2018 ) and neurotoxins in coupled pelagic–benthic food webs (Zguna et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even the intestinal flora of humans has been hypothesized to be a potential source of BMAA (Nunes-Costa et al 2020) and related hypotheses have emerged which implicate the human microbiota in neurodegenerative disease (Obrenovich et al 2020). In recent studies, BMAA has been detected within several of these organisms including microbial biofilms, marine and freshwater diatoms, dinoflagellates, and zooplankton (Réveillon et al 2016;Chatziefthimiou et al 2018;Jungblut et al 2018;Violi et al 2019;Zguna et al 2019;Metcalf et al 2020;. This expanding field of research will provide interesting data to help us understand the complex interactions of non-protein amino acids in a variety of organisms and ecosystems.…”
Section: Bmaa Is Produced By Cyanobacteriamentioning
confidence: 99%